Commodification of Religion in The Realm of Local Politics: A Study of the Tarekat Naqsabandiyah in Rokan Hulu Regency - Tito Handoko; Mega Hidayati; Muhammad Azhar; Abdul Munir Mulkan; M . Rafi; Deni Setiawan; Fajar Rahmanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This article aims to analyze the relationship between the teacher and the congregation of the Naqsabandiyah in local political action and their relationship with local political elites. This study uses a qualitative approach that aims to interpret a case that will be carefully examined and analyzed using periodic descriptive analysis methods. The results of this study indicate that the pattern of relations between teachers and congregation of the Naqsabandiyah groups in local political action in Rokan Hulu Regency tends to be more accommodating to the authorities, where the political orientation of this group has undergone a transition from traditional to rational action with its own political choices. Then, the relationship between the group and local political elites in socio-religious practices has confirmed the existence of a very strong religious and political relationship, where the Naqsabandiyah sees Achmad (local political elite) as a group representation traced from the existence of kinship ties.